CONCEPT OF CONSUMER LOYALTY OF UMRAH PILGRIMAGE ORGANIZERS: AN EMPIRICAL STUDY OF FACTORS SUPPORTING PILGRIM LOYALTY - Alamsyah, Alamsyah; Muharram, Susilawati (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
This study aims to identify and analyze the factors that influence the interest and loyalty of pilgrims towards the hajj and Umrah travel organizers (PPIU). Next, to explore strategies that PPIU can implement in improving the quality of their services to create customer satisfaction and loyalty. The method used is a qualitative method with a literature study approach; data sources were collected through empirical data and research and processed using a deductive method to formulate research results with relevant information. The results of this study indicate that service quality, trust in the hajj and Umrah travel organizers (PPIU), previous positive experiences, brand equity, service quality, and promotion mix are essential factors that influence the interest and loyalty of pilgrims. This study also found that to increase consumer loyalty, PPIU must focus on improving the quality of service and human resources, as well as identifying and resolving pilgrim problems with strategies such as adjusting guidance programs, intensive mentoring, fulfilling specific needs of pilgrims, and continuous quality improvement. The novelty of this study lies in the in-depth analysis of the factors that influence the interest and loyalty of pilgrims towards the organizers of the hajj and umrah (PPIU), with a particular focus on the influence of service quality, trust, previous positive experiences, brand equity, service quality, and promotion mix. The limitations of this study may not include other factors that can also influence pilgrim loyalty, such as external factors (economic or political conditions) or the diverse characteristics of individual pilgrims.